COMPARATIVE ANALYSIS OF TRADING VOLUME ACTIVITY DURING COVID-19 - Triono, Bambang; Hendrayanti, Silvia; Fauziyanti, Wachidah; Estuti, Eni Puji (Sekolah Tinggi Ilmu Ekonomi Semarang, 2021)
The first case of the covid-19 in Indonesia was announced on March 2nd 2020, The spread of the COVID-19 pandemic eventually brought very bad risks to the world economy, including Indonesia, especially in trade, and investment. This research aims to find outthe significant difference between Trading Volume activity (Case Study on LQ-45 issuers listed on the IDX). These data have been taken for 31 days before and 31 days after the first announcement of covid-19 corona virus in Indonesia. In this study has been used 43 sample of LQ45 companies that provide complete data on a daily basis and have published on the Indonesia Stock Exchange (IDX). This research uses Wilcoxon Signed Ranks Test. The data processing results showed that there is a significant difference trading volume activity between before and after the first announcement of the covid-19 case in Indonesia. This is indicated by the significance value of 0.00 < 0.05, which the trading volume activity has decreased compared to before the covid-19 case